A Study on Sentimental Analysis using Machine Learning Approach - Kumar, P Praveen; Gurunadh, PS; Maram, Balajee (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2021)
Nowadays, people using online platforms for exchanging ideas, sharing their views and learning through online platforms. Social media is filling up with huge data which are the various tweets, various blogs, and updates on posts and products etc. That data is unstructured and it needs to be organized and analyzed. Companies and many other people are trying to work on that data for long time to improve their position in the market. Sentimental Analysis plays a crucial role in this data classification. Sentimental analysis is a Natural Language Processing technique. This analysis classifies reviews data and opinions into positive, neutral and negative. This analysis can be done using machine learning. Machine learning is making the machines to learn from their past experiences. Machine learning importance is getting increased exponentially. This study aims to learn different levels of sentiments and steps that are involved in sentimental analysis and some machine learning algorithms for sentiment classification. How to cite this article: Kumar PP, Gurunandh PS, Maram B. A Study on Sentimental Analysis using Machine Learning Approach. J Adv Res Appl Arti Intel Neural Netw 2021; 5(1): 1-4.